2011
DOI: 10.11606/rco.v5i11.34789
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de gerenciamento e controle interno: uma análise dos escritórios de contabilidade de Belo Horizonte/MG e região metropolitana a partir da Taxonomia de Kaplan e Cooper

Abstract: O objetivo deste estudo foi analisar o nível de gerenciamento e controle interno dos escritórios de contabilidade a partir da tipologia de quatro estágios desenvolvida por Kaplan e de Cooper (1998) para projetar sistemas gerenciais. Na metodologia, adotou-se o estudo descritivo, por meio de pesquisa de campo do tipo survey e de natureza quantitativa. A pesquisa foi realizada em 112 escritórios de contabilidade situados na cidade de Belo Horizonte/MG e região metropolitana, registrados no Conselho Regional de C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Studies conducted by Silva, Rocha and Melo (2011) and Ghafran O'Sullivan (2013) highlighted that management control should be the responsibility of the senior management and that the audit committee should supervise the completeness and integrity of the audit report, and supervise other aspects related to the audit. They also add that audit committees are increasingly assuming the quality of companies' financial information.…”
Section: Audit Committee and Board Of Auditorsmentioning
confidence: 99%
“…Studies conducted by Silva, Rocha and Melo (2011) and Ghafran O'Sullivan (2013) highlighted that management control should be the responsibility of the senior management and that the audit committee should supervise the completeness and integrity of the audit report, and supervise other aspects related to the audit. They also add that audit committees are increasingly assuming the quality of companies' financial information.…”
Section: Audit Committee and Board Of Auditorsmentioning
confidence: 99%
“…The research contributes to the management accounting literature, specifically on informal controls, and also by specifying informal controls to organizational commitment and performance. The focus on a region of Brazil is one of the differentials of this study since Frare et al (2020) conducted a survey regarding the target audience of the research and identified that new variables could be added to management control and that, preferably, they investigated new regions of Brazil, considering that most doctors are concentrated in the South and Southeast regions of the country (Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A pesquisa contribui para a literatura de contabilidade gerencial, especificamente, sobre os controles informais e, também, ao especificar os controles informais em relação ao comprometimento e desempenho organizacional. O foco em uma região do Brasil é um dos diferenciais desse estudo, visto que Frare et al (2020) realizaram um levantamento quanto ao público-alvo da pesquisa e identificaram que novas variáveis poderiam ser acrescentadas em relação ao controle gerencial, e que, de preferência, investigassem novas regiões do Brasil, tendo em vista que a grande parte dos doutores se concentra nas regiões Sul e Sudeste do país (Silva et al, 2011).…”
Section: Introductionunclassified